Transformasi Digitalisasi Dalam Penerbitan Surat Perintah Pencairan Dana (SP2D) Badan Pengelolaan Keuangan, Pendapatan, Dan Aset Daerah Sukoharjo: Menuju Efisiensi Dan Transparansi - Kamila Luthfia Yahya; Iswary Amalia; Lies Nurhaini (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
The Regional Financial, Revenue and Asset Management Agency (BPKPAD) is a government agency that manages the regional finances and assets of Sukoharjo Regency in accordance with the principle of autonomy. Regional autonomy is expected to create efficiency and transparency in regional resource management. However, not all regions have managed their regional resources efficiently and with transparency, one of which is BPKPAD, which still manages its financial documents manually, especially in managing documents for the issuance of Fund Disbursement Orders (SP2D). The aim of this research is to analyze more deeply the obstacles experienced when publishing SP2D manually and provide appropriate solutions. This research uses a descriptive method with data collection techniques obtained from observations and interviews with employees in the Treasury Sector. This research produced findings in the form of obstacles experienced, namely inefficient time constraints and hard file document constraints resulting in a lack of transparency in their management. Therefore, the document collection process can be carried out digitally to create efficient performance and transparency in its management.